(untitled) (Progressive Agriculture, 2013)
Five hormone doses viz., 40, 60, 70, 85 and 90 mg of Pituitary gland (PG)/kg body endangered Tarabaim (Macrognathus aculeatus) were tested and they were designated as Treatments T1, T2, T3, T4 and T5, respectively. Significantly (p<0.05) higher fertilization (86%) and hatching rates (50%) were obtained from T5 (90 mg of PG extract/kg body weight) than those of other treatments. However, T4 (85 mg of PG extract/kg, body weight) and T3 (70 mg of PG extract/kg body weight) gave the highest (90%) ovulation rate. In May and June, the highest fertilization rate of 82% and 86% respectively and hatching rate 45% and 75%, respectively were obtained at the temperature ranged from 27.0 to 33.0ºC. In conclusion, PG extract at a dose of 90 mg/kg body weight appeared to be the suitable dose for artificial propagation of M. aculeatus, May and June are the suitable months for its artificial propagation. DOI: http://dx.doi.org/10.3329/pa.v19i2.16951 Progress. Agric. 19(2): 111 - 118, 2008